ASSESSMENT OF THE PERFORMANCE OF THE APPARATUS OF THE PAMONG PRAJA POLICE UNIT (SATPOL PP) IN CONTROLLING UNLICENSED STREET VENDORS (PKL) IN MOJOKERTO CITY - ananda nurhaliza; Tukiman (SOSIOEDUKASI, 2025)
After the COVID-19 pandemic, the number of street vendors selling along Jalan Benteng Pancasila, Mojokerto City, has increased significantly. This condition has prompted the need for enforcement by local government officials. This study aims to assess the performance of Pamong Praja Police Unit (Satpol PP) officers in regulating the presence of street vendors at this location. The research method used is descriptive qualitative with seven informants. It uses T.R Mitchell's (1978) theory of employee performance assessment, which includes quality of work, promptness, initiative, capability, and communication. Data collection was conducted through observation, in-depth interviews, and documentation, while data analysis used the interactive model of Miles and Huberman. The results of the study show that the performance quality, competence, and communication of Satpol PP employees in carrying out street vendor control tasks on Jalan Benteng Pancasila in Mojokerto City are at a good level. However, the indicators of timeliness and initiative are still at a fairly optimal level.